Report on the practice in industry training in fish preservation. - Escanillas, Natalia B. (College of Fisheries, University of the Philippines, 1959)
Of the various features of today's industrial program, the effort geared at improving our fishing industry stand out prominently. The current Philippine economic status definitely enjoins that the great bulk of our population must go into fishing production. The tremendous contribution of this industry to the economic welfare of the people cannot be underestimated. If properly developed, it will not only raise the people's living standard but also minimize the importation of canned fishery products. The premier position of fish in the Filipino diet cannot be overemphasized. It is the principal source of protein. Unless they have plenty of rice and fish on their table, millions of Filipinos do not consider themselves adequately fed. Fresh fish supply is however not constant. In an effort to offset the deficiencies in fish supply during off-season, preservation of extra catch during periods of glut has become an important innovation and has therefore come to the fore of Philippine economic life. The Philippines, which is one of the richest fishing grounds in the world, must, by necessity, have more canning factories and operate more refrigerating units. To implement this fishery program, the government has established functional fishery schools in several fishing sites in the country. The principles of fish preservation, fish capture and fish culture are being taught. Essentials of fish marketing are equally being stressed. Corollary to the above project is the building of canneries, investing and importing modern refrigerating units and sending Filipino scholar abroad, e.g., United States and Japan to learn the modern techniques of fishery education.